First Ladies and the Press The Unfinished Partnership of the Media Age - Beasley, Maurine H. (Northwestern University Press, 2005)
At her first press conference, Eleanor Roosevelt, uncertain of her role as hostess or leader, passed a box of candied grapefruit peel to the thirty-five women journalists. Nearly sixty years later, Hillary Clinton, an accomplished professional woman and lawyer, tried to mollify her critics by handing out her chocolate-chip cookie recipe. These exchanges tells us as much about the social-and political-roles of women in America as they do about the relation of the first lady to the press and the public. Looking at the personal interaction between each first lady from Martha Washington to Laura Bush and the mass media of her day, Maurine H. Beasley traces the growth of the institution of the first lady as a part of the American political system. Her work shows how media coverage of first ladies, often limited to stereotypical ideas about women, has not adequately reflected the importance of their role.